Applications of metaheuristic optimization algorithms in civil engineering - Kaveh, A. 1948- (Springer, 2017)
The book presents recently developed efficient metaheuristic optimization algorithms and their applications for solving various optimization problems in civil engineering. The concepts can also be used for optimizing problems in mechanical and electrical engineering.
Keywords: Civil engineering -- Mathematical models.; Mathematical optimization.; Heuristic algorithms.; elektronické knihy; electronic books